Crescimento e desordem nutricional em pimenteira malagueta cultivada em soluções nutritivas suprimidas de macronutrientes - Flores, Rilner A. [UNESP]; Almeida, Thiago B. F. de [UNESP]; Politi, Lucas S. [UNESP]; M. Prado, Renato de [UNESP]; Barbosa, José C. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2012)
Despite the importance of pepper in the world, there is little information about the culture's foliar diagnosis. By this fact, the macronutrient omission effect on chili pepper growth and nutritional status, grown under nutrient solution were evaluated. The treatments were: full nutrient solution and nutrient solution without N, P, K, Ca, Mg, and S, under a completely randomized design with three replications. Plants were grown in a Hoagland & Arnon nutrient solution, in 8L pots. 56 days after transplant, the plant height, stem diameter, leaf number, leaf area, the relative chlorophyll content, the plant dry matter, the macronutrient contents of the shoots and roots were evaluated, and made of description of nutritional disorders. The macronutrients omission interfered in the nutrients concentrations in different parts of the plant, which limited the vegetative growth and decreased the dry matter production, causing the characteristic deficiency symptoms for each nutrient. The nutrients that most limited the pepper growth were nitrogen, calcium, and potassium, however, calcium was the most required element by the plant.
Growth and nutritional disorder in chili pepper grown in nutrient solutions with macronutrient omission
Keywords: Capsicum frutescens; Mineral nutrition; Nutritional deficiency